A 2-wheel self-balancing robot - Ho, Yuan Fa (2014)
Inverted pendulum, 2 wheeled robot and other types of balancing robot have been increasingly popular among hobbyist and researchers with the increasing demonstration of the capability of what they can do. Hobbyist want to find out how to create one at a cheaper cost, while researchers are trying to find out better ways to improve stability in controlling the device. The goals of the project are: 1. Create a single 2 wheel balancing robot from scratch. 2. Balance the robot – with as little movement in terms of the tilt and distances travel. 3. Create applications to remotely control and analyse data from the robot. A PID Controller was implemented for the close-loop system. This control system allows the robot to achieve the two goals of remaining upright, and staying or changing of position. The robot was also able to maintain balance at slopes and uneven body weightage.